2020
DOI: 10.1007/s11255-020-02561-4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chronic kidney disease on long-term outcome of patients with valvular heart defects

Abstract: Introduction Valvular heart diseases (VHD) are becoming a significant problem in the Polish population. Coexistence of chronic kidney disease (CKD) in patients with VHD increases the risk of death and affects further therapeutic strategy. Aim Analysis impact of CKD on long-term prognosis in patients with VHD. Material and methods The inclusion criteria were met by 1025 patients with moderate and severe VHD. Mean observation time was 2528 ± 1454 days. Results The average age of the studied population was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
1
5
1
Order By: Relevance
“…Gender differences in the prevalence of proteinuria may be related to prescribing patterns, differences in responses and adherence to therapies, as well as hormonal factors [ 32 ]. However, as expected, the main factor associated with the prevalence of proteinuria in previous studies was diabetes mellitus [ 3 , 10 , 22 , 31 ]. Unfortunately, this association could not be evaluated in our study.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Gender differences in the prevalence of proteinuria may be related to prescribing patterns, differences in responses and adherence to therapies, as well as hormonal factors [ 32 ]. However, as expected, the main factor associated with the prevalence of proteinuria in previous studies was diabetes mellitus [ 3 , 10 , 22 , 31 ]. Unfortunately, this association could not be evaluated in our study.…”
Section: Discussionsupporting
confidence: 81%
“…Nevertheless, the prevalence of CKD in this study was even higher than the average prevalence reported in previous studies on patients with heart diseases (31% versus 26% [range, 8–38%]), which could be explained by the higher age (72 vs. 61 [range, 42–63] years) and lower frequency of male patients (51% vs. 54% [range, 37–76%]) in the present study than in the previous reports ( Table S4 ) [ 3 , 10 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. On the other hand, the prevalence of proteinuria in our study was lower than the average values observed in previous reports (28% vs. 34% [range, 8–62%]) [ 3 , 22 , 23 , 24 , 27 , 30 ].…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…[ 12 14 ] Mitral valve (MV) disease comes second, with the exception of a few regional variations in which MV disease is the leading VHD in patients with renal insufficiency. [ 6 , 12 15 ] Caseous calcification of the mitral annulus and MAC-related calcified amorphous tumour are two variants of MAC that occur particularly in patients with ESRD ( Figure 1 ). [ 16 ] Moreover, it is observed that the greater the impairment in renal function, and therefore the lower GFR, the greater the prevalence of VHD, with most affected patients being at a later stage of CKD (Stage 5 or GFR <15 ml/min/1.73 m 2 ) rather than in an earlier stage (Stage 1 and 2, or GFR >60 ml/min/1.73 m 2 ).…”
Section: Mitral and Aortic Valve Diseasementioning
confidence: 99%
“…[ 5 , 6 , 11 , 16 ] Other possible pathological mechanisms that have been proposed include malnutrition, cachexia, hyperuricaemia and increased sclerostin concentrations. [ 15 , 18 , 41 , 42 ] The presence of systemic shunting due to dialysis arteriovenous fistulas, which create a volume overload state on the right heart chambers, in turn causing right ventricular dilatation and dysfunction, may also contribute to VHD. [ 13 ] This leads first to worsening of TR, followed by exacerbation of MR.[ 13 ] The fact that different pathophysiological mechanisms causing VHD in CKD patients have been put forward highlights the complexity of the calcification process and may suggest that different mediators may be required at different stages of the process ( Figure 3 ).…”
Section: Mitral and Aortic Valve Diseasementioning
confidence: 99%